Synthesis and evaluation of C2-carbon-linked heterocyclic-5-hydroxy-6-oxo-dihydropyrimidine-4-carboxamides as HIV-1 integrase inhibitors. Issue 3 (1st February 2015) - Naidu, B. Narasimhulu; Sorenson, Margaret E.; Patel, Manoj; Ueda, Yasutsugu; Banville, Jacques; Beaulieu, Francis; Bollini, Sagarika; Dicker, Ira B.; Higley, Helen; Lin, Zeyu; Pajor, Lori; Parker, Dawn D.; et al.
Graphical abstract